Influencing factors of medication literacy among community-dwelling older adult patients with hypertension: a study based on social learning theory - Lu, Tingting; Yang, Zhen; Chen, Ping; Li, Jingyan; Zheng, Chen; Kong, Linghui; Zhang, Huijun (Frontiers in Pharmacology, 2023)
Objective: This study aimed to examine the factors affecting medication literacy in community-dwelling older adults with hypertension, guided by social learning theory. It sought to analyze the pathways these factors influenced and provide a theoretical foundation for designing targeted intervention programs. Study design：This is a cross-sectional study. Methods: From October 2022 to February 2023, a total of 432 community-dwelling older adults with hypertension from Linghe District, Guta District, and Taihe District, Jinzhou City, Liaoning Province, China, were selected using convenience sampling. Data were collected using a socio-demographic questionnaire, a medication literacy questionnaire, the Brief Illness Perception Questionnaire, the General Self-efficacy Scale, and the Perceived Social Support Scale. The collected data were analyzed with Kruskal-Wallis and Mann-Whitney tests, correlation analysis, multiple stepwise regression analysis, and structural equation modeling (SEM). Results: The medication literacy score among the participants was 3.83 ± 1.91. Multi-factor analysis revealed key factors affecting their medication literacy, including blood pressure-control status, utilization of community health education resources, receiving guidance for medication usage, marital status, number of annual visits, social support, self-efficacy, and disease perception. The SEM based on social learning theory showed that general self-efficacy mediated the relationship between social support, disease perception, and medication literacy. Conclusion: The present study developed a model and provided potential intervention strategies to improve medication literacy, knowledge, and safety among community-dwelling older adults with hypertension, considering the relationships between the identified variables.